PERAN PERKEMBANGAN PASAR MODAL TERHADAP PEMERATAAN PENDAPATAN DI ASEAN - Satrianto, Elton Buyung; Akbar, Saiqa Ilham (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
A significant amount of research has been conducted to investigate the relationship between capital market development and economic growth. However, there is still shortage of research that specifically identifies the direct impact of capital markets on income inequality. This study was conducted to determine whether capital market developments contribute to income equality in ASEAN countries, especially in Indonesia. Using secondary data sourced from stock exchanges in Southeast Asia as well as income inequality data (Gini index) data from each country during the period 2000 - 2020, it is processed by using regression to find out how the size, liquidity and activity of the capital market have an impact on income inequality. The development of capital markets in developing countries has a negative impact on income equality according to previous research.